2014
DOI: 10.1111/pim.12079
|View full text |Cite
|
Sign up to set email alerts
|

Eotaxin‐1 is involved in parasite clearance during chronic filarial infection

Abstract: Eosinophil migration as key feature of helminth infection is increased during infection with filarial nematodes. In a mouse model of filariasis, we investigated the role of the eosinophil-attracting chemokine Eotaxin-1 on disease outcome. BALB/c and Eotaxin-1(-/-) mice were infected with the rodent filaria Litomosoides sigmodontis, and parasitic parameters, cellular migration to the site of infection, and cellular responsiveness were investigated. We found increased parasite survival but unaffected eosinophil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…3d), despite the fact that eosinophil numbers in the TC were comparable between the two infected groups of mice (Fig. 2d), confirming previous results which showed that eosinophil migration to the site of infection is independent of eotaxin-1 secretion (Gentil et al 2014). Levels of granzyme B were equal between infected WT and IL-17A −/− mice (Fig.…”
Section: Resultssupporting
confidence: 89%
“…3d), despite the fact that eosinophil numbers in the TC were comparable between the two infected groups of mice (Fig. 2d), confirming previous results which showed that eosinophil migration to the site of infection is independent of eotaxin-1 secretion (Gentil et al 2014). Levels of granzyme B were equal between infected WT and IL-17A −/− mice (Fig.…”
Section: Resultssupporting
confidence: 89%
“…These cells rapidly kill parasites that have been damaged by anthelmintic drugs, and this may trigger a more vigorous proinflammatory response that results in AEs. This hypothesis is supported by the finding that eotaxin-1–deficient mice have reduced eosinophil responses to TLR2 activation and filarial antigen exposure, and the finding that macrophages from these mice produce less IL-6 [ 29 ]. Additional research will be needed to understand the apparent link between eotaxin-1 and AEs.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, mice on a semi-resistant 129/SvJ background have an increased L. sigmodontis worm burden in the absence of the eosinophil products eosinophil peroxidase (EPO) and major basic protein (MBP) [32]. Similarly, eotaxin1-deficient mice had an increased L. sigmodontis adult worm burden [33]. Lack of the type 2 cytokine IL-5, which is also essential for eosinophil generation and survival, was previously shown to impair adult worm clearance during L. sigmodontis infection [3437].…”
Section: Introductionmentioning
confidence: 99%